A quality-improvement project to enhance systemic arterial contrast opacification in CT for trans-catheter aortic valve implantation. Issue 9 (September 2022) - Komber, H.M.E.I.; Neumann, S.; Paull, J.; Andrade, M. Gesteira; Lyen, S.M.; Manghat, N.E.; Hamilton, M.C.K.
Abstract : AIM: To assess improvement in arterial opacification by optimising the contrast medium dosing protocol for computed tomography (CT) prior to trans-catheter aortic valve implantation (TAVI). MATERIALS AND METHODS: A wide variation in arterial opacification was observed in the initial CT TAVI protocol (standard protocol). The practice was optimised by considering the time required for the examination and optimising contrast medium flux. This became the optimised protocol with a 30-second contrast medium bolus of iodine flux 15–19 mg iodine/kg body weight/second (mg/kg/s). Attenuation (mean HU) in (a) the ascending aorta (gated systolic acquisition) and (b) the ascending, descending thoracic (at carina), infra-renal abdominal aorta, and right common iliac artery (non-gated acquisition) was measured. Thirty-one sequential optimised examinations were compared to 31 prior standard protocol examinations. RESULTS: There was no difference between the standard and optimised groups regarding age, sex, weight, body mass index (BMI), or voltage. The mean bolus durations were 24.9±4.4 seconds for the standard and 30±0.3 seconds for the optimised protocols ( p< 0.001). Although there was no difference in the attenuation in the gated ascending aorta (p>0.99), there was improvement at all other anatomical points in the non-gated examinations of the optimised protocol ( p< 0.002). CONCLUSION: Optimising contrast medium flux and matching bolus duration to the CT technology dramatically improves the vascular access component of TAVI planning and provides a reliable method to achieve objectively enhanced arterial opacification. This work highlights how to obtain good arterial contrast medium opacification in haemodynamically fragile patients without excessive contrast medium volumes. Highlights: Optimal arterial opacification is important for radiological assessment. A weight-based contrast flux with the bolus length matched to scan duration is key. This delivers reliable arterial opacification with modest contrast dose. The contrast technique can be easily modified for your needs.